Services marketing : text and cases - Baron, Steve 4 0 (J. Steve)16; Harris, Kim; 5 (Houndsmill, Basingstoke, Hampshire, UK : Palgrave, 2009)
An exploration of issues, models, and theories of service marketing that discusses goals, customer interactions, consumer experience, relationship marketing, profitability, and other related topics, and includes case studies.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Marketing.;Marketing -- Service industries;Service industries -- 20 -- Case studies; 20; 2